UV-B Protective and Antioxidant Activities of Protein Hydrolysate From Sea Cucumber (Holothuria scabra) Using Enzymatic Hydrolysis - Doungapai, Chitpon; Siriwoharn, Thanyaporn; Malila, Yuwares; Autsavapromporn, Narongchai; Makkhun, Sakunkhun; Yarnpakdee, Suthasinee; Jantanasakulwong, Kittisak; Regenstein, Joe M.; Wangtueai, Sutee (Frontiers in Marine Science, 2022)
The optimization of sea cucumber hydrolysate preparation using three commercial enzymes was done using response surface methodology (RSM) with face-centered central composite design (face- centered CCD). Effect of hydrolysis time and concentration of enzyme on degree of hydrolysis (DH), yield, antioxidant and photoprotective activities of the sea cucumber hydrolysates were determined. The optimum conditions for sea cucumber hydrolysis using concentration of papain (SCP), alcalase (SCA), or flavourzyme (SCF) were 3.6, 5.0, and 4.1% (w/w protein), respectively and hydrolysis for 360 min. The resulting hydrolysates exhibited DH of 81-91%, yield of 13-14%, the IC50 of DPPH radical scavenging activity of 0.3-4.1 mg/mL, the FRAP assay of 0.5-0.6 mmol FeSO4/mL, and the IC50 of ABTS radical scavenging activity of 1.3-1.6 mg/mL. The photoprotective activity was reported as the percentage of the HaCaT cell viability after UV-B treated. The SCP, SCA, and SCF hydrolysates showed 72.4, 74.5, and 71.3% cell viability, respectively. The concentration of hydrolysates with 80% survival of HaCaT cell (IC80) was 0.21, 0.15 and 0.20 mg/mL for SCP, SCA and SCF, respectively. Thus, the bioactive peptides from SCP were then selected for isolation and characterization. The SCP contained hydrophilic and hydrophobic amino acids of 42.4 and 57.6%, respectively. The ultrafiltration and Sephadex G-25 gel filtration chromatography were done for peptide isolation from the SCP. Six peptides were identified using LC-MS/MS as Leu-Val-Asn-Glu-Leu-Thr-Glu-Phe-Ala-Gln (1163 Da), Leu-Val-Asn-Glu-Val-Thr-Glu-Phe-Ala-Gln (1149 Da), Phe-Val-Asp-Ser-Ser-Ala-Thr-Thr (826 Da), Phe-Asn-Asp-Leu-Gly-Ala-Trp (821 Da), Phe-Pro-Asp-Thr-Thr-Thr-Leu (793 Da), and Lys-Phe-Gly-Glu-Gly-Lys (664).